Aesthetic medicine – limits of physician and dentist competence in the light of the positions of the medical self‑government (Journal of Face Aesthetics, 2024)
The lack of unified legislation concerns in aesthetic medicine (including surgical aesthetic medicine of the face), has recently caused this problem to occupy special attention of the Supreme Medical Council. This work mainly deals with the legal aspects and problems encountered by physicians and dentists in the field of aesthetic medicine and facial aesthetics, paying special attention to the definition of aesthetic medicine, aesthetic medicine as a health benefit and also the rights of physicians and dentists under the current legislation.
Keywords: aesthetic medicine; physicians; dentists; Supreme Medical Council